Chitosan-sodium alginate-diatomite composite adsorbent as well as preparation method and application thereof

The preparation of chitosan-sodium alginate-diatomaceous earth composite adsorbents through dropping addition method solved the problems of insufficient mechanical strength and poor reuse stability of traditional adsorbents, and efficient removal of harmful substances in dye wastewater, and significantly improved the Stability and reliability of adsorbents.

CN119455906AActive Publication Date: 2025-02-18GUANGXI UNIV FOR NATITIES

Patent Information

Application Number
CN202411789765.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-06
Publication Date
2025-02-18
Estimated Expiration
2044-12-06

AI Technical Summary

Technical Problem

The existing adsorbents are insufficient in mechanical strength when treating dye wastewater, and have poor reuse stability, making it difficult to effectively remove harmful substances in dyes.

Method used

The sodium alginate solution of calcined diatomaceous earth was slowly dripped into the mixture of chitosan and CaCl2 by dropping addition method to prepare a chitosan-sodium alginate-diatomaceous earth composite adsorbent.

Benefits of technology

It significantly enhances the adsorption performance and structural stability of hydrogel microbeads, improves the reuse stability of adsorbents, has a removal rate of more than 95%, and has a slight decline in performance after multiple cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119455906A_ABST
    Figure CN119455906A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a chitosan-sodium alginate-diatomite composite adsorbent. The preparation method comprises the following steps: (1) carrying out calcination pretreatment on diatomite; (2) dissolving sodium alginate powder in water; (3) adding the calcined diatomite into a sodium alginate solution to prepare a mixed solution a; (4) adding CaCl2 into an acetic acid solution for dissolving; (5) adding chitosan powder into a CaCl2 solution, and uniformly stirring to obtain a mixed solution b; (6) dropwise adding the mixed solution a into the mixed solution b for crosslinking to prepare SA / DM / CS composite gel balls; and (7) washing the gel balls with water for several times, repeatedly freezing and thawing for several times, and drying to obtain the composite adsorbent. The composite adsorbent is prepared by dropwise adding the sodium alginate solution containing the calcined diatomite into the mixed solution of the chitosan and the CaCl2, so that the problem of low mechanical strength of single sodium alginate hydrogel is solved, and the recycling stability of the hydrogel microsphere adsorbent is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of adsorbent preparation, and specifically relates to a chitosan-sodium alginate-diatomaceous earth composite adsorbent, a preparation method and application thereof. Technical Background

[0002] As a major textile production and dye user, my country's annual dye usage accounts for 83% of the world's total. [1] The textile printing and dyeing industry consumes a lot of water and produces a lot of wastewater in every link of the printing and dyeing process. Every year, 11% of industrial wastewater comes from wastewater generated by textile products. [2] Dyes are well soluble in water. Dye wastewater has complex components and has the characteristics of high chromaticity, high chemical oxygen demand, difficulty in degradation, high toxicity, and difficulty in treatment. Therefore, dye wastewater, which is difficult to treat and highly harmful, is one of the main industrial wastewaters in my country at this stage. [3-4] At present, the main methods for treating dye wastewater are divided into physical method, chemical method and biological method. [5] Common treatment methods include adsorption, coagulation, electrochemical method, advanced oxidation method, membrane separation method, etc. [6] Among various treatment methods for dye wastewater, adsorption has the advantages of high efficiency, low energy consumption and economy, so it has become a commonly used treatment method for dye wastewater, which can remove harmful inorganic / organic substances in industrial wastewater. However, most adsorbents have poor performance and low selectivity, and there is still a lot of room for development in wastewater treatment. In order to develop green, cheap and practical dye adsorbents, researchers have recently focused on natural and biodegradable polymers. [7] .

[0003] Sodium alginate is a natural polysaccharide extracted from brown algae (such as kelp or sargassum) by crushing the algae, extracting with strong alkali, and reacting with calcium chloride to precipitate sodium carbonate. [8] The SA molecule is composed of β-D-mannuronic acid (M) and α-L-guluronic acid (G). [9] , is a linear anionic copolymer. β-D-mannuronic acid and α-L-guluronic acid residues are covalently linked together in different sequences or blocks to form

[10] The composition and structural differences between the M block and the G block will significantly change the gel properties of SA. The polymer with more M blocks has better elasticity but poorer water solubility, while the polymer with more G blocks has higher hardness and brittleness but better water solubility. The presence of a large number of free carboxyl groups enables SA to cross-link with a variety of metal cations to form gels.

[11] , where Ca 2+ Ions are safe and non-toxic, with a wide range of sources, and are the most commonly used ionic crosslinking agents.

[12] The metal ion-mediated SA gelation process is mainly affected by factors such as SA concentration, M / G ratio, and metal ion concentration, but is not strictly required for pH and temperature conditions.

[13] This simplifies the preparation process of sodium alginate gel materials to a certain extent and enhances the controllability of the preparation process, laying the foundation for the widespread application of sodium alginate gel materials.

[0004] References

[0005] [1] Yin Ping. Research progress of advanced oxidation treatment technology for dye wastewater[J]. Guangdong Chemical Industry, 2021, 48(8): 186-187, 183.

[0006] [2] Shi Rui, Li Yili, Yin Jing, et al. Preparation of corn straw and activated carbon and study on its adsorption kinetics[J]. Chinese Journal of Environmental Engineering, 2014, 8(8); 3428-3432.

[0007] [3] Xu Nannan, Lin Dasong, Xu Yingming, et al. Effects of corn stover and biochar on Cd 2+ Adsorption characteristics and influencing factors of [J]. Journal of Agro-Environment Science, 2014, 33(5): 958-964.

[0008] [4] Cui Yumin, Yin Rongcan. Research progress in dye wastewater treatment methods[J]. Science and Technology Review, 2021, 39(18): 79-87.

[0009] [5] China Resources Comprehensive Utilization, 2020, 38(11): 94-96.

[0010] [6] AZBARN, YONART, KESTOGLUK. Comparison of COD and decolorization of polyester and acetate dyeing wastewater by various advanced oxidation processes and chemical treatment methods [J]. Chemosphere, 2004, 55(1): 35-43.

[0011] [7] B.Galzerano,CICabello,M.Munoz,GGBuonocore,P.Aprea,B.Liguori,L.Verdolotti,Fabrication of green diatomite / chitosan-based hybrid foams with dye sorptioncapacity,Materials 13(2020)3760,https: / / doi.org / 10.3390 / ma13173760.

[0012] [8]FISET JF,BLAIS JF,RIVEROS P A.Review on the Removal ofMetal Ions from Effluents Using Seaweeds,Alginate Derivatives and Other Sorbents[J]. Revue des sciences de l eau,2008,21(3).

[0013] [9]Ruvinov E,Cohen S.AdvancedDrug Delivery Reviews,2016,96,54.

[0014]

[10] Teng K, An Q, Chen Y, et al. ACS Biomaterials Science & Engineering, 2021, 7(4), 1302.

[0015]

[11] Lee KY,MooneyD J.Progress in Polymer Science,2012,37(1),106.

[0016]

[12] Ching SH, Bansal N, Bhandari B. Critical Reviews in Food Science and Nutrition, 2017, 57(6), 1133.

[0017]

[13] Guo X, Wang Y, Qin YM, et al. International Journal of Biological Macromolecules, 2020, 162, 618. Summary of the invention

[0018] The purpose of the present invention is to provide a chitosan-sodium alginate-diatomite composite adsorbent, a preparation method and an application thereof. By using a dropwise addition method, a sodium alginate solution incorporating calcined diatomite is slowly dripped into a mixture of chitosan and CaCl2, and a chitosan-sodium alginate-diatomite composite adsorbent is successfully prepared. The innovative method of the present invention effectively solves the problem of insufficient mechanical strength of a single sodium alginate hydrogel and significantly enhances the repeated use stability of the hydrogel microbead adsorbent.

[0019] In order to achieve the above object, the present invention provides the following technical solutions:

[0020] A method for preparing a chitosan-sodium alginate-diatomaceous earth composite adsorbent comprises the following steps:

[0021] (1) calcining diatomaceous earth to obtain calcined diatomaceous earth;

[0022] (2) dissolving sodium alginate powder in water to prepare a sodium alginate solution;

[0023] (3) Weighing the calcined diatomaceous earth and adding it to the sodium alginate solution to prepare a mixed solution a;

[0024] (4) weighing CaCl2, adding it to an acetic acid solution, stirring and dissolving it to prepare a CaCl2 solution;

[0025] (5) Weigh chitosan powder and add it to the CaCl2 solution and stir evenly to obtain a mixed solution b;

[0026] (6) dropping the mixed solution a into the mixed solution b for cross-linking to prepare SA / DM / CS composite gel spheres;

[0027] (7) The SA / DM / CS composite gel spheres were rinsed with water several times, and then repeatedly frozen and thawed several times and then dried to obtain a chitosan-sodium alginate-diatomaceous earth composite adsorbent.

[0028] Preferably, the mass of the sodium alginate powder in step (1) is 1-5 g.

[0029] Preferably, the M / G ratio of the sodium alginate powder is 1-2:1.

[0030] Preferably, the mass of the calcined diatomaceous earth in step (3) is 1-5 g.

[0031] Preferably, in step (6), the time for cross-linking of the mixed solution a by dripping into the mixed solution b is 1 hour.

[0032] The invention also provides an application of a chitosan-sodium alginate-diatomaceous earth composite adsorbent in adsorbing methylene blue.

[0033] Preferably, the pH of the adsorbent when adsorbing the methylene blue solution is 3-11.

[0034] Preferably, the concentration of the methylene blue solution is 100-500 mg / L.

[0035] Preferably, the adsorbent adsorbs the methylene blue solution for 180-240 minutes.

[0036] Compared with the prior art, the present invention has significant technical advantages, which are specifically reflected in the following aspects:

[0037] (1) In terms of preparation process, the present invention cleverly adopts an innovative composite method. By carefully dropping a sodium alginate solution containing calcined diatomite into a carefully proportioned chitosan and CaCl2 mixed solution, a sodium alginate-chitosan composite hydrogel microbead is prepared, and a composite adsorbent with a methylene blue removal rate of more than 95% is obtained. This unique process not only cleverly combines the advantages of chitosan, sodium alginate and diatomite, but also significantly improves the problem of insufficient mechanical strength of traditional single sodium alginate hydrogel. By introducing calcined diatomite, not only the adsorption performance of the hydrogel microbeads is enhanced, but also its overall structural stability is improved, and at the same time, a diffusion channel for dye molecules in the microbeads is provided, so that the prepared chitosan-sodium alginate-diatomite composite adsorbent exhibits higher durability and reliability when dealing with various complex environments. This innovation not only lays a solid foundation for the recyclability of hydrogel microbead adsorbents, but also greatly broadens its scope and possibilities in practical applications, marking an important technological breakthrough in the field of adsorption materials.

[0038] (2) In terms of performance, the chitosan-sodium alginate-diatomaceous earth composite adsorbent of the present invention exhibits excellent adsorption effect and outstanding stability. After five rigorous cycle tests, the removal rate of methylene blue by the adsorbent dropped from the initial 95.54% to only 90.46%, with a decrease of only 5.08%. This data fully proves that the adsorbent of the present invention can still maintain good adsorption capacity after repeated use, and the performance degradation is minimal. This high degree of stability and continuous and efficient adsorption performance not only means that the frequency of adsorbent replacement can be reduced in practical applications, reducing operating costs, but also means that the adsorbent has great potential and practical application value in treating industrial wastewater such as dye wastewater.

[0039] In summary, the chitosan-sodium alginate-diatomaceous earth composite adsorbent of the present invention not only solves the problem of low mechanical strength of traditional adsorption materials through an innovative preparation process, but also demonstrates its great potential in practical industrial applications through good adsorption effect and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is the effect of sodium alginate dosage on methylene blue removal rate;

[0041] Figure 2 This is the effect of sodium alginate G / M ratio on the removal rate of methylene blue;

[0042] Figure 3 This is the effect of diatomaceous earth addition on the removal rate of methylene blue;

[0043] Figure 4 This is the effect of solution pH on the removal rate of methylene blue;

[0044] Figure 5 This is the effect of initial concentration on the adsorption of methylene blue;

[0045] Figure 6 It is a pseudo first-order kinetic model diagram;

[0046] Figure 7 It is a pseudo second-order kinetic model diagram;

[0047] Figure 8 is the adsorption isotherm at 298K;

[0048] Fig. 9 is the adsorption isotherm at 303K;

[0049] Fig.10 is the adsorption isotherm at 308K;

[0050] Fig.11 This is the cyclic adsorption experiment diagram of the adsorbent. DETAILED DESCRIPTION

[0051] The present invention will be further described in detail below in conjunction with specific embodiments. It should be emphasized that the following description is merely exemplary and is not intended to limit the scope of the present invention and its application.

[0052] 1. Preparation method of chitosan-sodium alginate-diatomaceous earth composite adsorbent

[0053] 10g of diatomaceous earth (DM) was calcined at 450℃ for 4h, with a heating rate of 10℃ / min. At room temperature, 1-5g of sodium alginate powder (M / G ratios of 1:2, 1:1, 2:1, respectively) was dissolved in 200mL of deionized water to prepare a sodium alginate solution. Weigh 1-5g of calcined diatomaceous earth and add it to the sodium alginate solution for later use. Weigh 2g of CaCl2 and add it to 100mL of 2% acetic acid solution and stir to dissolve it to prepare a CaCl2 solution. Then weigh 0.6g of chitosan powder and add it to the CaCl2 solution and stir evenly. Sodium alginate solution was dripped into the solution to prepare SA / DM / CS composite gel ball adsorbent, and cross-linked for 1h. The SA / DM / CS composite gel ball was rinsed several times with ultrapure water. After the composite gel ball was repeatedly frozen and thawed three times, it was dried in a vacuum dryer for 24h (temperature -55℃, vacuum degree <10Pa).

[0054] Technical principle of the preparation method of the present invention:

[0055] The innovative preparation method of chitosan-sodium alginate-diatomaceous earth composite adsorbent of the present invention not only combines the advantages of various natural polymers and inorganic materials, but also achieves a significant improvement in adsorption performance by finely controlling the amount of raw materials and process parameters in each step, demonstrating significant technological progress. The following is an in-depth analysis of each link of the preparation process and an explanation of the necessity of optimization:

[0056] (1) Pretreatment of diatomaceous earth (DM)

[0057] First, 10g of diatomaceous earth was selected as the basic support material. Its unique porous structure gives the adsorbent excellent specific surface area and adsorption capacity. By calcining at 450°C for 4 hours, the heating rate was precisely controlled at 10°C / min. This process effectively removed impurities in the diatomaceous earth and enhanced its structural stability, providing a more solid foundation for subsequent composites. The optimization of this step ensures the efficient role of diatomaceous earth in the composite system and is a key step in improving the overall adsorption performance.

[0058] (2) Preparation of sodium alginate solution

[0059] Dissolve 1-5g of sodium alginate powder in 200mL of deionized water to prepare a sodium alginate solution. Sodium alginate (M / G ratio of 1:2, 1:1, 2:1) not only acts as a binder, but also can significantly improve the hydrophilicity and biocompatibility of the adsorbent due to its rich hydroxyl and carboxyl functional groups. By adjusting the amount of sodium alginate and the M / G ratio, the physical structure and chemical properties of the adsorbent can be finely controlled, thereby affecting its adsorption efficiency and selectivity for target pollutants. The optimization of this step is the key to balancing adsorption performance and material cost, and provides the possibility of achieving efficient and low-cost adsorption.

[0060] (3) Preparation and compounding of chitosan solution

[0061] Dissolve 2g of CaCl2 in 100mL of 2% acetic acid solution to form a CaCl2 solution, then add 0.6g of chitosan powder and stir thoroughly. As a natural high molecular polymer, chitosan can form ionic crosslinks with sodium alginate through its amino and hydroxyl groups, thus enhancing the mechanical strength and stability of the adsorbent. The introduction of chitosan also gives the adsorbent more active sites, improving its adsorption capacity for specific pollutants. By precisely controlling the amount of chitosan added, the surface charge distribution and pore structure of the adsorbent can be further optimized, thereby achieving more efficient capture of target pollutants.

[0062] (4) Preparation and post-treatment of composite gel spheres

[0063] Sodium alginate solution was dropped into a mixture containing chitosan and CaCl2 to form SA / DM / CS composite gel ball adsorbent through cross-linking reaction. The cross-linking time was set to 1 hour to ensure sufficient reaction. Subsequently, ultrapure water was used for multiple rinses to remove unreacted chemicals and impurities to ensure the purity of the adsorbent. In particular, after three repeated freeze-thaw treatments, the internal pores and adsorption sites of the gel balls can be further enhanced. Finally, it was dried at -55°C in a vacuum freeze dryer (vacuum degree <10Pa) for 24 hours. This step not only removed the moisture in the adsorbent, but also retained its porous structure, ensuring the long-term stability of the adsorbent during storage and use.

[0064] (5) Significant improvement in technical effects

[0065] Through the above-mentioned finely controlled preparation process, the obtained chitosan-sodium alginate-diatomaceous earth composite adsorbent exhibits good technical effects. It not only has high adsorption performance, but also exhibits good regeneration performance and reusability, significantly reducing the treatment cost. In addition, the green and environmentally friendly characteristics of the preparation method, as well as the precise control of the raw material dosage and the optimization of the process parameters, make the adsorbent have broad application prospects in the field of dye wastewater treatment.

[0066] 2. Adsorption experiment

[0067] Take 0.1g of adsorbent and place it in 100mL of MB solution of a certain concentration. After oscillating at 220rpm in a water bath constant temperature oscillator and adsorbing for a certain period of time, measure the concentration of remaining methylene blue in the solution after adsorption, and calculate the adsorption capacity q of the adsorbent for the methylene blue solution. t (mg·g-1) and removal rate R (%), the formula is as follows:

[0068]

[0069] Among them, q t is the adsorption capacity of the adsorbent for MB, mg / g; R is the removal rate of the adsorbent for MB, %; C0 is the initial concentration of the MB solution, mg / L; C e is the concentration of MB solution at adsorption equilibrium, mg / L; V is the volume of MB solution, L; m is the mass of adsorbent, g.

[0070] 3. Factors affecting adsorption performance

[0071] 3.1 Effect of Sodium Alginate Dosage

[0072] Figure 1The figure shows the removal rate of MB by adsorbents with different sodium alginate addition amounts. When the addition amount is 1g, sodium alginate cannot be cross-linked in the mixed solution due to the low dosage; when the addition amount is 5g, the sodium alginate solution is too viscous to prepare hydrogel microbeads by dropwise addition. As can be seen from the figure, the hydrogel with an addition amount of 3g has the highest removal rate. The reason is that with the increase of sodium alginate content, the number of adsorbable sites in the hydrogel increases, thereby improving the adsorption performance of the hydrogel. However, excessive sodium alginate causes the volume of the hydrogel microbeads to increase due to the excessive viscosity of the solution, resulting in a decrease in the specific surface area of ​​the hydrogel, which affects the adsorption performance of the hydrogel. Therefore, 3g was selected as the optimal addition amount of sodium alginate for the hydrogel microbead adsorbent in subsequent experiments.

[0073] 3.2 Effect of G / M ratio

[0074] The mass fraction of G and M components in sodium alginate can be expressed by their ratio (G / M). The G / M ratio is an important parameter for characterizing sodium alginate. The removal rate of methylene blue by adsorbents containing sodium alginate with different G / M ratios varies with time. Figure 2 As shown in the figure, as the G / M ratio increases, the removal rate of methylene blue by the hydrogel also gradually increases. This is because as the content of the G component (α-L-guluronic acid) increases, the hydrophilicity of SA is significantly enhanced, thereby enhancing the adsorption performance of the hydrogel. Therefore, sodium alginate with a G / M ratio of 2:1 was used for subsequent research.

[0075] 3.3 Effect of diatomaceous earth addition on methylene blue removal rate

[0076] Figure 3 The effect of different diatomaceous earth addition amounts on the removal rate of methylene blue is shown. Compared with the adsorbent without diatomaceous earth, the removal rate is increased from 86.48% to 90.90%. After the addition of diatomaceous earth, the surface roughness of the adsorbent increases, providing more adsorption sites. With the increase in the amount of diatomaceous earth added, the removal rate increases from 90.90% to 95.46%. However, excessive diatomaceous earth will reduce the removal rate. This is because excessive diatomaceous earth is prone to aggregation inside the adsorbent, which has a negative impact on adsorption. It can be seen from the figure that when the addition amount is 3g, the adsorbent adsorption effect is optimal. Therefore, 3g will be used as the optimal addition amount of diatomaceous earth in subsequent experiments.

[0077] 3.4 Effect of solution pH

[0078] Solution pH directly affects the final removal rate through surface charge and the form of MB in solution. Figure 4As shown in the figure, as the pH value increases from 3 to 9, the removal rate of MB by the adsorbent gradually increases from 93.48% to 95.07%, while when the pH rises to 11, the removal rate drops to 87.65%. This shows that within a wide pH range, the adsorbent exhibits good adsorption performance for methylene blue. This is because the surface of the adsorbent is electronegative under the condition of pH <11, and hydrogen bonding interactions are formed between the adsorbent and the positively charged methylene blue. Under higher pH conditions, the hydrolysis of methylene blue molecules is inhibited, and there is electrostatic repulsion, which leads to a decrease in the adsorption capacity of the adsorbent for methylene blue. Considering that the fresh solution of methylene blue is weakly acidic, the pH used in the experiment is 5.

[0079] 3.5 Effect of initial concentration

[0080] like Figure 5 As shown in the figure, with the increase of initial concentration, the equilibrium adsorption amount gradually increases, and the adsorption amount of methylene blue changes with the contact time. Due to the large concentration gradient as the driving force and the high-frequency continuous collision between the adsorbent and the adsorbate molecules, the adsorption driving force of methylene blue is affected by the initial concentration. The hydrogel adsorbent has an extremely fast adsorption rate in the first 90 minutes. As the adsorption proceeds, the adsorption sites on the adsorbent surface are occupied by methylene blue molecules, and the adsorption gradually slows down until the adsorption equilibrium is basically reached around 180 minutes. Among them, the adsorption rate of 500 mg / L MB is the fastest.

[0081] 4. Adsorption kinetics

[0082] The adsorption capacity of the adsorbent for methylene blue at different times was measured at 298 K, and the effect of different initial concentrations of methylene blue on the adsorption kinetics was analyzed. 0.1 g of the adsorbent was added to MB solutions with different initial concentrations, and the concentration of residual MB in the solution was measured by UV-Vis.

[0083] In order to describe the mechanism of the adsorption process of methylene blue by adsorbent microbeads, the adsorption kinetics of MB removal was studied under the experimental conditions of 25°C and pH = 5 using 100 ml methylene blue solution with different initial concentrations (100 mg / L, 200 mg / L, 300 mg / L, 400 mg / L, 500 mg / L). The experimental data of different initial concentrations were analyzed. Among them, the pseudo first-order (3) and pseudo second-order (4) models are generally expressed as:

[0084]

[0085]

[0086] Where q e and q t(All units are mg / g) represent the equilibrium adsorption capacity and the adsorption capacity at time t (min), respectively. K1 and k2 represent the rate constants of the pseudo-first-order model and the pseudo-second-order model, respectively. In the Weber-Morris model, k d represents the rate constant of the intra-particle diffusion model. The intercept C represents the boundary layer thickness. The larger C is, the greater the boundary layer effect.

[0087] Plotting ln(q e -q t ) against t and t / q against t can obtain the calculation results of k1 and k2. The relevant graphs are shown in Figure 6 、 7 . The parameters related to the kinetic model are shown in Table 1. The correlation coefficient of the pseudo-second-order equation is closer to 1. In addition, compared with the experimental values, the pseudo-second-order model obtained more accurate adsorption capacity values. Therefore, the pseudo-second-order model is more suitable for the adsorption of methylene blue by the adsorbent. The adsorption rate of methylene blue by the adsorbent is controlled by chemisorption through electron sharing or exchange between the adsorbent and the adsorbate.

[0088] Table 1 Kinetic model parameters for the adsorption of methylene blue by the adsorbent

[0089]

[0090] 5. Adsorption isotherm

[0091] The experiments were carried out at 295, 303, and 308 K, respectively. 0.1 g of the adsorbent was added to 100 mL of an MB solution with a concentration of 500 mg / L. After adjusting the initial pH to 5, the adsorption experiment was carried out in a constant-temperature oscillator at a rotation speed of 220 rpm. The concentration of residual MB in the solution was determined by UV-Vis. The adsorption isotherm describes the equilibrium concentration of the adsorbate in the solution and the interaction behavior between the adsorbate and the adsorbate molecules. The Langmuir model (5) assumes that the adsorbed substance forms a monolayer at specific homogeneous sites, while the Freundlich model (6) assumes that adsorption occurs on the multi-layer coverage of the adsorbed substance on the heterogeneous surface. The adsorption isotherms of MB on the adsorbent at 298 - 308 K were fitted with these two isothermal adsorption models respectively. In the Langmuir model, a separation factor R L (7) can be defined to determine the favorability and reversibility of the adsorption process. When 0 < RL < 1, it is a favorable adsorption process. The larger R L is, the more favorable the adsorption of pollutants by the adsorbent.

[0092]

[0093] where C e (mg / L) is the dye equilibrium concentration, q e(mg / g) is the equilibrium adsorption capacity, qm (mg / g) is the maximum adsorption capacity, K L and K F (L / mg) corresponds to the Langmuir constant and the Freundlich constant. Langmuir constant K L (L / mg) is related to the affinity and free energy of adsorption, the slope of the Freundlich isotherm indicates the adsorption intensity, and 1 / n is a heterogeneous factor that indicates whether the adsorption process is favorable.

[0094] The adsorption isotherm fitted according to the adsorption data is shown in Figure 8-10 The parameters are shown in Table 2. It can be seen that the equilibrium adsorption capacity of the adsorbent increases with the increase of adsorption temperature, indicating that adsorption is an endothermic process. The correlation coefficient of the Langmuir model (R 2 ) is higher than the correlation coefficient of the Freundlich model. The Langmuir model fits the experimental data best. Therefore, the adsorption of MB by the adsorbent is a monolayer adsorption on the heterogeneous adsorption sites on the uniform surface. In addition, the 1 / n value obtained by the Freundlich model is between 0 and 1, which indicates that the adsorption of MB by the adsorbent is a preferred process.

[0095] Table 2 Langmuir model and Freundlich model parameters of methylene blue on adsorbent

[0096]

[0097] 6. Repeatability Experiment

[0098] The regeneration and reuse rate of the adsorbent are important factors to be considered in practical industrial applications. 0.1 g of the adsorbent was immersed in 100 mL of methylene blue solution (100 mg / L) with an initial pH of 5.0 and adsorbed at 298 K until adsorption equilibrium was reached. Then it was desorbed in 0.1 M HCl solution. Under acidic conditions, H + The interaction between the adsorption sites is stronger than the electrostatic interaction between methylene blue and the adsorbent, resulting in the desorption of methylene blue from the adsorbent. Fig.11 After five cycles, the removal rate of methylene blue by the adsorbent decreased from the initial 95.54% to 90.46%, a decrease of only 5.08%, and still had good adsorption effect and stability. This proves that the adsorption microbeads modified in this experiment also have great potential in practical industrial applications for dye wastewater treatment.

[0099] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a chitosan-sodium alginate-diatomaceous earth composite adsorbent, characterized in that: The following steps are involved: (1) calcining diatomaceous earth to obtain calcined diatomaceous earth; (2) dissolving sodium alginate powder in water to prepare a sodium alginate solution; (3) Weighing the calcined diatomaceous earth and adding it to the sodium alginate solution to prepare a mixed solution a; (4) weighing CaCl2, adding it to an acetic acid solution, stirring and dissolving it to prepare a CaCl2 solution; (5) Weigh chitosan powder and add it to the CaCl2 solution and stir evenly to obtain a mixed solution b; (6) dropping the mixed solution a into the mixed solution b for cross-linking to prepare SA / DM / CS composite gel spheres; (7) The SA / DM / CS composite gel spheres were rinsed with water several times, and then repeatedly frozen and thawed several times and then dried to obtain a chitosan-sodium alginate-diatomaceous earth composite adsorbent.

2. The method for preparing the chitosan-sodium alginate-diatomaceous earth composite adsorbent according to claim 1, characterized in that: The mass of the sodium alginate powder in step (1) is 1-5g.

3. The method for preparing the chitosan-sodium alginate-diatomaceous earth composite adsorbent according to claim 2, characterized in that: The M / G ratio of the sodium alginate powder is 1-2:

1.

4. The method for preparing the chitosan-sodium alginate-diatomaceous earth composite adsorbent according to claim 1, characterized in that: The mass of the calcined diatomaceous earth in step (3) is 1-5 g.

5. The method for preparing the chitosan-sodium alginate-diatomaceous earth composite adsorbent according to claim 1, characterized in that: In step (6), the cross-linking time of the mixed solution a being dripped into the mixed solution b is 1 hour.

6. A chitosan-sodium alginate-diatomaceous earth composite adsorbent prepared according to the method according to any one of claims 1 to 5.

7. Use of the chitosan-sodium alginate-diatomaceous earth composite adsorbent according to claim 6 in adsorbing methylene blue in wastewater.

8. Use of the chitosan-sodium alginate-diatomaceous earth composite adsorbent in adsorbing methylene blue from wastewater according to claim 7, characterized in that: The pH value of the methylene blue solution when the adsorbent adsorbs the methylene blue solution is 3-11.

9. Use of the chitosan-sodium alginate-diatomaceous earth composite adsorbent in adsorbing methylene blue from wastewater according to claim 8, characterized in that: The concentration of the methylene blue solution is 100-500 mg / L.

10. Use of the chitosan-sodium alginate-diatomaceous earth composite adsorbent in adsorbing methylene blue from wastewater according to claim 7, characterized in that: The time for the adsorbent to adsorb the methylene blue solution is 180-240 minutes.

Citation Information

Patent Citations

  • Three-component cationic dye adsorbent and preparation method thereof

    CN103447008A

  • Graphene oxide-diatomite composite adsorption microspheres with three-dimensional porous structures and preparation method

    CN106955671A

  • Magnetic efficient adsorbent SA (at) CMC (at) CTS as well as preparation method and application thereof

    CN116020419A

Cited By

  • Method for converting secondary aluminum ash into soil

    CN119699151A

  • Novel spherical adsorption material based on crab shells as well as preparation method and application of novel spherical adsorption material

    CN120132800A

  • A spherical adsorbing material based on crab shell and a preparation method and application thereof

    CN120132800B

  • Method for immobilizing D-psicose-3-epimerase

    CN120843497A

  • Treating agent for in-situ remediation of aquaculture wastewater and preparation method of treating agent

    CN121342144A